BLOOD SUGAR LEVELS OF DIABETES MELLITUS TYPE II PATIENTS THAT CONSUME KERSEN LEAVES (Mumtingia calabura L) IN CURUP OF BENGKULU CITY - Khasanah, Heti Rais; Laksono, Heru; W, Putri Widelia (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2020)
Background: Diabetes mellitus is a chronic metabolic disease or disorder with multietiology (many causes) which is characterized by high blood sugar levels accompanied by impaired carbohydrate, fat, and protein metabolism as a result of inadequate insulin function. Cherry leaves as an alternative medicine for diabetes mellitus, are used by boiling the carcinoma leaves using water. Boiling process attracts polar compounds found in cherry leaves, cherry leaves contain saponins and flavonids which can inhibit the absorption of blood sugar from the intestine, thus inhibiting the absorption of carbohydrates. Method: this research uses descriptive type with Cross Sectional research design. Sample selection with snowball sampling method. There were 32 respondents, namely type II diabetes mellitus who consumed cherry leaf boiled water (20 routines, and 12 non-routine). Method of blood sugar levels using a glucometer. Results: blood sugar levels in patients with type II diabetes mellitus who consume boiled water cherry leaves regularly at 20 probandus (40% normal and 60% abnormal) obtained an average of 166.6 mg / dl and standard deviation of 35,905, not routine (100% abnormal) an average of 211.3 mg / dl was obtained and a standard deviation of 76,935. Conclusion: cherry leaves boiled water when consumed regularly and regularly can reduce blood sugar levels of patients with type II diabetes mellitus.Keywords: Blood glucose, DM type II, Cherry leaves.